2011
DOI: 10.1016/j.placenta.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in placental vascular development and function

Abstract: Nitric oxide (NO) is one of the most pleiotropic signaling molecules at systemic and cellular levels, participating in vascular tone regulation, cellular respiration, proliferation, apoptosis and gene expression. Indeed NO actively participates in trophoblast invasion, placental development and represents the main vasodilator in this tissue. Despite the large number of studies addressing the role of NO in the placenta, its participation in placental vascular development and the effect of altered levels of NO o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 189 publications
(142 reference statements)
3
125
1
1
Order By: Relevance
“…Furthermore, since preeclampsia is a very heterogeneous disease, it may be critical to focus therapeutic studies with sildenafil specifically in subgroups of patients who have augmented circulating sFLT1 and increased pressor response to Ang II. In normal pregnancy, despite enhanced Ang II and volume expansion, NO production is amplified (21,(43)(44)(45)(46)(47), likely by growth factors such as VEGF and placental growth factor that are required for normal placental angiogenesis (24,25,48). The actions of NO to reduce blood pressure during pregnancy are pleiotropic, primarily through endothelium-dependent dilation and resulting smooth muscle relaxation, which decreases vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since preeclampsia is a very heterogeneous disease, it may be critical to focus therapeutic studies with sildenafil specifically in subgroups of patients who have augmented circulating sFLT1 and increased pressor response to Ang II. In normal pregnancy, despite enhanced Ang II and volume expansion, NO production is amplified (21,(43)(44)(45)(46)(47), likely by growth factors such as VEGF and placental growth factor that are required for normal placental angiogenesis (24,25,48). The actions of NO to reduce blood pressure during pregnancy are pleiotropic, primarily through endothelium-dependent dilation and resulting smooth muscle relaxation, which decreases vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that GH and PL act directly on the GHR in endothelial cells, promoting both vasodilation and NO release. Although the effects induced by PL on the vasculature are not fully understood, our data are among the first to suggest the role played by this hormone in the endothelium and in the NO-dependent relaxation of the aorta, a process that may be related to the redistribution of blood flow that occurs during pregnancy [7,54] . It is important to note that the experimental approaches utilized, as well as the conditions under which the experiments were undertaken, are important factors to consider, because the vasoconstrictor effects induced by GH and PL via the inhibition of NO have been reported in other vascular beds and in the setting of other experimental approaches [15,16,18] , findings suggestive of the differential actions of these hormones in different vascular beds.…”
Section: Discussionmentioning
confidence: 79%
“…The human placenta is derived from the outer cell layer of the morula, called trophoblast, which proliferates after implantation, invades the decidua, and simultaneously differentiates into cytotrophoblast and syncytiotrophoblast, forming the primary villi [46]. These villi are invaded by mesenchymal cells derived from the embryo (secondary villi) which through vasculogenesis generate vascular capillaries, forming the tertiary villi [46].…”
Section: Cxcl12-mediated Signaling In the Human Placentamentioning
confidence: 99%
“…These villi are invaded by mesenchymal cells derived from the embryo (secondary villi) which through vasculogenesis generate vascular capillaries, forming the tertiary villi [46]. During the first weeks endovascular trophoblasts migrate into the uterine spiral arteries and plug these arteries, likely to avoid precocious onset of maternal blood flow into the intervillous space [22].…”
Section: Cxcl12-mediated Signaling In the Human Placentamentioning
confidence: 99%